Enhancing diagnostic outcomes in kidney genetic disorders: the KidGen national kidney genomics study protocol - Amali Mallawaarachchi; Hugh McCarthy; Thomas A. Forbes; Kushani Jayasinghe; Chirag Patel; Stephen I. Alexander; Tiffany Boughtwood; Jeffrey Braithwaite; Aron Chakera; Sam Crafter; Ira W. Deveson; Randall Faull; et al. (BMC Nephrology)
Abstract Background Genetic kidney disease (GKD) significantly affects the community and is responsible for a notable portion of adult kidney disease cases and about half of cases in paediatric patients. It substantially impacts the quality of life and life expectancy for affected children and adults across all stages of kidney disease. Precise genetic diagnosis in GKD promises to improve patient outcomes, provide access to targeted treatments, and reduce the disease burden for individuals, families, and healthcare systems. Genetic investigations are increasingly used in nephrology practice; however, many patients who undergo testing still lack a definitive diagnosis. Methods The KidGen National Kidney Genomics Study aims to increase diagnostic yield for those with suspected monogenic kidney disease without a diagnosis after standard diagnostic genetic testing. The program will seek to enrol up to 200 families from KidGen Collaborative kidney genetics clinics across Australia who have yet to receive conclusive diagnoses despite prior testing. Participants will undergo a personalised pathway of research genomic investigations. These include re-analysing existing data and/or undergoing advanced genomic testing methods, including short and long-read whole-genome sequencing, RNA sequencing, and functional genomics strategies using mouse modelling or kidney organoids. Discussion The KidGen National Kidney Genomics Study is a coordinated, multidisciplinary extension of previous research projects that aims to assess the diagnostic yield of advanced genomic approaches. The study's evidence will drive changes to current diagnostic pathways, including identifying which chronic kidney disease patients are most likely to benefit from a more comprehensive genomic approach to diagnosis.